PREVALENCE OF GASTROINTESTINAL PARASITES IN THOROUGHBRED HORSES (EQQUS CABALLUS) DURING THE PERIOD OF 2010 IN THE RACETRACK “LA RINCONADA” CARACAS, VENEZUELA - Morales B, Abelardo A. (2011)
650 horses (Equus caballus Linnaeus, 1758), race Thoroughbred Race, 300 male and 350 female were studied, all of two years old, from breeding centers in the central region of Venezuela by stool by McMaster flotation technique (Willis-Molloy) during the quarantine period 2010 at the Racetrack "La Rinconada" Caracas, Venezuela. Parasitological study revealed the presence of Strongyle eggs in 477 horses (73%), Parascaris equorum (Goeze, 1782) eggs in 23 (4%) and 150 (23%) were negative. The presence of strongylos remained within the range of 550-1850 HPG (Eggs per g of stool), while P. equorum was 250-600 HPG. These results suggestive an inadequate health plan and specifically to control parasites. It is possible the parasite resistance to conventional use, but this may be associated with climate changes that alter the life cycle of these parasites. In conclusion, we reported the presence of gastrointestinal parasites in Thoroughbred horses during the quarantine period at the Racetrack "La Rinconada" Caracas, Venezuela.